THE CANNY ALGORITHM IMPLEMENTATION FOR OBTAINING THE OBJECT CONTOUR IN A MOBILE ROBOT’S WORKSPACE IN REAL TIME (Journal of Universal Science Research, 2024)
The article is devoted to the Canny algorithm implementation for obtaining the objects contours in mobile robots’ workspace in real time. The paper presents the mathematical foundations of the algorithm, including all key stages: from image pre-processing up to the Canny operator application. The article main focus is the algorithm integration into the mobile robot system and its adaptation to the dynamic conditions of the workspace. The developed program in the Python programming language using the PyCharm development environment demonstrates the high performance of the algorithm in real time. A series of experiments has confirmed that the average video stream processing speed fluctuates in a narrow range from 1000.07 to 1002.70 frames per second.